2018
DOI: 10.7553/84-1-1716
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Certificate of Information Literacy programme and engaging with faculty: a case study of the Cape Peninsula University of Technology

Abstract: The purpose of this study was to evaluate the effectiveness of a certificate-based information literacy (IL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…The authors of this paper have observed this weakness of students over many years and over different study levels. The same is posited in the work of Hartman (2001), Seamans (2002), Fielding et al (2013) and Davids and Omar (2018). Yevelson-Shorsher & Bronstein's (2018) study of three population groups reported that students' challenges are due to insufficient training and lack of awareness of library resources.…”
Section: The Students' Voicementioning
confidence: 61%
See 3 more Smart Citations
“…The authors of this paper have observed this weakness of students over many years and over different study levels. The same is posited in the work of Hartman (2001), Seamans (2002), Fielding et al (2013) and Davids and Omar (2018). Yevelson-Shorsher & Bronstein's (2018) study of three population groups reported that students' challenges are due to insufficient training and lack of awareness of library resources.…”
Section: The Students' Voicementioning
confidence: 61%
“…The objective of this case study was to gain insight into students' perspectives on their experiences of the IL training in the CIL programme. It follows from our previous paper (Davids & Omar 2018) in which lecturers and librarians assessed the CIL programme. The two papers together give us a holistic view of the perspectives of all the stakeholders on the CIL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Учење усмерено на ). Учење усмерено на студенте је успешно примењено и у стицању информатичке писмености студенте је успешно примењено и у стицању информатичке писмености ( (Davids & Omar, 2018Davids & Omar, 2018. Потоњи рад описује експеримент у коме је при-…”
Section: евалуација примене учења усмереног на студенте у различитим областима високог образовањаunclassified